Dukungan Sosial dan Subjective Well-Being pada Purnawirawan TNI - Indriashanty Astriewardhany; Alfi Purnamasari (Universitas Ahmad Dahlan, 2021)
Social Support and Subjective Well-Being on Retired TNI OfficersThis study examined the relationship between social support and the subjective well-being among retired of the Indonesian Air Force. Participants of this study were 71 retirees who are members of the Indonesian Air Force Retired Union (PPAU: Perhimpunan Purnawirawan Angkatan Udara), selected using incidental sampling. Data collected using the Subjective Well-Being scale and Social Support Scale and analyzed using Product Moment. The result showed that there was a positive relationship between social support and subjective well-being. It can be concluded that higher social support is followed by higher subjective well-being and vice versa. The social support gave 63.04% effective contribution to the subjective well-being while the rest 36.96% is determined by other factors.